Knowledge Awareness of the Requirements and Developments of Electronic Document Management for Workers in the Documents Departments in the Sultanate of Oman: الوعي المعرفي بمتطلبات ومستجدات الإدارة الإلكترونية للوثائق للعاملين في دوائر الوثائق بسلطنة عُمان - Saleh Said Alrashdi, Sulaiman; Lubis, Asmuliadi; Mansor, Fadillah (Al-Muqaddimah: Online Journal of Islamic History and Civilization, 2022)
The researcher seeks to present a vision to enable modern administrations to apply what known as a smart management in Oman. Studying the extent of knowledge by specialists and workers in Oman. The study seeks to highlight the importance of the knowledge side of workers in applying the policies of smart departments, which seeks primarily to simplify procedures by reducing the need for paper documents. Whether in circulation or relying on them to complete the administrative work entrusted to them, and answering the question posed about the level of knowledge of specialists and workers in the field of document management in government agencies In Oman, the requirements and developments of archiving and electronic document management. The study assumes that specialists and workers in the field of document management and archives in the Sultanate are familiar with the requirements of archiving systems and electronic document management; due to the scientific qualification of a large number of them, it also presupposes the need to strengthen the knowledge of developments in this field. Due to the acceleration witnessed in this field in conjunction with the great technological development. The study depends on the descriptive and analytical approaches in the research by collecting the necessary data through a questionnaire that will distributed to the study community, then describing the existing situation and analyzing it to reach conclusions and develop the necessary proposals to enhance what related to raising the level of knowledge of workers in the field. The study community consists of specialists (who have qualifications scientific field) in Oman.